Characterization of the resistance to Vip3Aa in Helicoverpa armigera from Australia and the role of midgut processing and receptor binding - Chakroun, Maissa (Sci Rep, 2016)
Crops expressing genes from Bacillus thuringiensis (Bt crops) are among the most successful technologies developed for the control of pests but the evolution of resistance to them remains a challenge. Insect resistant cotton and maize expressing the Bt Vip3Aa protein were recently commercialized, though not yet in Australia. We found that, although relatively high, the frequency of alleles for resistance to Vip3Aa in field populations of H. armigera in Australia did not increase over the past four seasons until 2014/15. Three new isofemale lines were determined to be allelic with previously isolated lines, suggesting that they belong to one common gene and this mechanism is relatively frequent. Vip3Aa-resistance does not confer cross-resistance to Cry1Ac or Cry2Ab. Vip3Aa was labeled with (125)I and used to show specific binding to H. armigera brush-border membrane vesicles (BBMV). Binding was of high affinity (K(d) = 25 and 19 nM for susceptible and resistant insects, respectively) and the concentration of binding sites was high (R(t) = 140 pmol/mg for both). Despite the narrow-spectrum resistance, binding of (125)I-labeled Vip3Aa to BBMV of resistant and susceptible insects was not significantly different. Proteolytic conversion of Vip3Aa protoxin into the activated toxin rendered the same products, though it was significantly slower in resistant insects.